Characterization and Composition Analysis of Municipal Solid Waste for Bioethanol Production - Biose, Osadebe; Imhontu, Maureen; Akenzua, Oghosa; Atsegha, Bildad; Okorie, Christopher; Onabe, James; Angalapu, Jonah D.; Kubeyinje, Bawo; Omojevwe, Shella Amrasa; Iyeke, Igbinoimwahia D. (European Journal of Applied Sciences, 2021)
Every unwanted or non-useful solid substance generated in any human population is referred to as solid waste. Globally, the management of solid waste is an enormous challenge for municipalities. Previous studies have indicated that an increase in population with relating attendant urbanization dynamics and growth of continuous aggregation will further aggravate this challenge. This paper aims at determining the potentials of using municipal solid waste as a feedstock in the commercial production of Bioethanol. The research team which was made up of the coordinator, co-coordinators and research assistants carried out a preliminary survey which consist of mapping the study areas and obtaining some information through the observation of the various sites. The study area which was the residential areas of the University of Benin community were then mapped into Senior Staff Quarters (which comprised of Professorial quarters, senior staff quarters and Blocks of flats), junior staff quarters and Student Hall of Residence. A preliminary survey form was originated for this purpose. Printing of questionnaires, sample notes, pamphlets, stickers and tagging of bin baskets and wheelie bins were done. A three (3) Stage sorting and characterization of respondents’ waste were carried out. Composition of waste was determined after which the digital weighing balance was used to determine the mass of the waste which was recorded, before allowing proper disposal of the waste. Samples of sorted waste (organic) were collected into sample bottles and taken to the laboratory for microbial analysis. The solid waste generated is made of nine major components for which color coded bags was used to differentiate them (fruit, food, plastic, paper, glass, metals, combustibles, leaves, and ceramics). The study showed that 58.85% of the total solid waste generated in the residential areas of the University of Benin was made of biodegradable matter (food and fruit) which can be harnessed for the production of Bioethanol. The recyclables (Papers and Plastics) which are 36.34 % of the waste can also be recycled into other useful products. Efforts should be made by stakeholders to evolve sustainable waste management policies for disposal, waste reduction and recycling projects.